Pengaruh Penambahan Kayu Manis dan Cengkeh terhadap Minuman Tepache Kulit Nanas (Ananas Comosus L.) - Gusmiyanti Sam; Rukmelia Rukmelia (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2026)
Fermented drinks can be made from pineapple skin extract which is then called pineapple skin juice fermented drink. This study aims to determine the effect of cinnamon and cloves on pineapple skin tepache drinks, and to determine the organoleptic properties of pineapple skin tepache with the addition of cinnamon and cloves. Making pineapple skin tepache is done by fermenting for 24 hours using 150 grams of pineapple skin, 25 grams of brown sugar, 50 grams of granulated sugar, 250 ml of boiled water (group I), adding 2 cm, 2.5 cm, 3 cm of cinnamon (group II) and adding 2 cloves, 3 grains, 4 grains (group III). This study uses the Completely Randomized Design (CRD) analysis method, and will be continued with the Duncan Test if there is a significant difference. After fermentation, pineapple skin tepache drinks are obtained with the characteristics of color, aroma and taste. All drinks were liked by respondents related to these characteristics, the pH of the drink was also still at 4.13 - 4.37, inactive antioxidant activity (IC50 > 250 ppm), and the content of lactic acid bacteria was still low around 107.33 to 178.33. Pineapple skin tepache drink had inactive antioxidant activity, the acidity of all drinks was at the acid level, and the lactic acid bacteria colony was below standard. All samples were still liked by respondents, both in terms of color, taste, and aroma.